Intermittent fasting and its influence on health and sports results - Kowalczuk, Maria; Lipińska, Justyna; Lipiński, Łukasz; Kopeć, Izabela (Journal of Education, Health and Sport, 2024)
Introduction Intermittent fasting (IF) is most simply defined as periods of eating alternating with periods of not eating. It has become one of the most popular weight-loss diets in recent years. One reason for the rapid growth in popularity of intermittent fasting may be its simplicity, as this dietary regimen does not require a change in a person’s current eating patterns, nor a change in foods. Aim of the study This review aims to present the current state of knowledge about intermittent fasting and answer the question of what effect this form of diet has on the human body and sports results and its benefits to health. Materials and methods The paper was created based on the Pubmed database. The literature was reviewed using the keywords: ”intermittent fasting”, ”16/8 fasting” and ”diet standards”. The current state of knowledge It has been shown that intermittent fasting can be helpful in controlling body weight and reducing metabolic diseases as a result of better glucose regulation and reduced inflammation. Weight reduction can also result in improved athletic performance. In addition, IF has positive effects on the cardiovascular system, specifically improving blood pressure, lowering heart rate, and regulating the body’s lipid metabolism indicators. Summary Although there is evidence of the beneficial effects of intermittent fasting, more research needs to be conducted to evaluate the mechanisms, efficacy in humans, target populations, and safety of intermittent fasting. Undoubtedly, a certain group of people may benefit greatly from this type of diet, as it does not require a change in current eating habits due to the simplicity of this diet.